IMPLEMENTASI BUDAYA ORGANISASI DALAM MENINGKATKAN PELAYANAN ADMINISTRASI PENDIDIKAN DI MTS AL JUMHURIYAH - Marina, Lia; Chaniago, Nasrul Syakur; Rifa’I, Muhammad (Hijri, 2021)
This research aims 1). To find out the organizational culture applied at MTS AI Jumhuriyah Batang Kuis Medan. 2). To find out the mechanism of administrative services at MTS AI Jumhuriyah Batang Kuis Medan. 3). To find out the role of madrasah heads in supporting the implementation of organizational culture at Mts AI Jumhuriyah Batang Quiz Medan. 4). To find out the impact of implementing organizational culture in improving education administration services at Mts AI Jumhuriyah Batang Quiz Medan. In this research, qualitative research is used with a qualitative descriptive approach. This research was conducted at Mts AI Jumhuriyah Batang Quiz Medan. The techniques used in collecting data are interview, observation and documentation techniques. The analysis in this research is data reduction, data presentation and drawing conclusions. The guarantees for the validity of the data in this research are credibility, transferability, dependability, and confirmation. The findings in this research indicate that the application of organizational culture in improving educational administration services at Mts AI Jumhuriyah Batang Quiz school has been implemented well, in which organizational culture is emphasized, namely on the values of discipline, cooperation, constancy of leadership and religious values. Each of these elements has contributed to the improvement of educational administration services at Mts AI Jumhuriyah. These cultures serve as a support to support in the smooth process of the entire performance system of each person so that all activities run well so that educational goals are achieved. When the organizational culture is successfully implemented, this HAI will certainly have an impact on improving educational administration services at Mts AI Jumhuriyah which has shown its quality, It can be seen from the harmonious relationship between fellow personnel, the smooth service communication system, the high sense of solidarity and the realization of both structural and cultural cooperation.Organizational Culture., Educational Administration